Hubungan antara Persepsi tentang Lingkungan Sekitar dan Subjective Well-Being pada Siswa SMP - Firda Damayanti; Ihsana Sabriani Borualogo (UNISBA Press, 2023)
Abstract. Child Friendly City (CFC) is a crucial component in building A WorldFit for Children, which is closely related to the subjective well-being of children (SWB). This study aims to determine the relationship between perceptions about the neighborhood and junior high school students’s SWB in Bandung. Google Forms and Questionnaires were used to collect data online and offline through cluster random sampling technique. The participants are junior high school students in Bandung City aged 12-16 years (N= 956; 57.1% female; 42.9% male). Perceptions about the neighborhood were measured using a measurement tool from Children's Worlds, SWB was measured using the Children's Worlds Subjective Well-Being Scale 5 Items (CW-SWBS5) and Overall Life Satisfaction (OLS). Data were analyzed using multiple linear regression analysis to determine the relationship between perceptions about the neighborhood and the SWB of junior high school students in the city of Bandung. The comparable means statistical test is used to test the difference in the average value of perceptions about the surrounding environment and the average SWB. The results of this study show a positive relationship between environmental perceptions and SWB. Perceptions about the neighborhood contribute to the SWB of junior high school students in Bandung City by 38.7% in certain domains and 29.3%. overall. The component of perceptions about the neighborhood that contributes the most and significantly to student SWB is about people in their environment helping them when they have problems (B =.245; p<.000). To increase SWB for junior high school students in Bandung, the government, schools and parents can work together to create an environment that is safe, friendly and has adequate facilities for children. Abstrak. Kota Layak Anak (KLA) merupakan salah satu komponen penting dalam membangun A WorldFit for Children yang berkaitan erat dengan subjective well-being anak (SWB). Penelitian ini bertujuan untuk mengetahui hubungan antara persepsi tentang lingkungan sekitar dan SWB siswa SMP di Kota Bandung. Pengambilan data dilakukan secara daring dan luring menggunakan Google Form dan Kuesioner dengan teknik cluster random sampling. Partisipan penelitian ini adalah siswa SMP di Kota Bandung berusia 12 – 16 tahun (N= 956; 57.1% perempuan; 42.9% laki-laki). Persepsi tentang lingkungan sekitar diukur menggunakan alat ukur dari Children’s Worlds, SWB diukur menggunakan Children’s Worlds Subjective Well-Being Scale 5 Items (CW-SWBS5) dan Overall Life Satisfaction (OLS). Data dianalisis menggunakan analisis regresi linear berganda untuk mengetahui hubungan persepsi tentang lingkungan sekitar terhadap SWB siswa SMP di Kota Bandung. Uji statistik compare means digunakan untuk menguji perbedaan nilai rerata persepsi tentang lingkungan sekitar dan SWB. Hasil penelitian menunjukkan bahwa terdapat hubungan positif antara persepsi tentang lingkungan dan SWB. Persepsi tentang lingkungan sekitar memberikan kontribusi terhadap SWB siswa SMP di Kota Bandung sebesar 38.7% pada domain tertentu dan 29.3%. secara keseluruhan. Komponen persepsi tentang lingkungan sekitar yang memberikan kontribusi paling besar dan signifikan terhadap SWB siswa, yaitu persepsi mengenai orang-orang di lingkungan mereka menolong mereka jika mereka memiliki masalah (B =.245; p<.000). Untuk meningkatkan SWB pada siswa SMP di Kota Bandung, pemerintah, sekolah, dan orang tua dapat bekerja sama untuk menciptakan lingkungan yang aman, ramah, dan memiliki fasilitas memadai untuk anak.